Study of Withdrawing Students for the University of Alberta 1970-71 Session - Well, A. Vander; Sartoris, P. C. (Canadian Journal of Counselling and Psychotherapy, 2012)
A withdrawal questionnaire was completed by 614 students withdrawing from the University of Alberta during the 1970-71 winter session. In addition to obtaining biographical information, reasons for withdrawal were grouped into six basic categories: financial, academic, personal, extracurricular, health, and living arrangements. Findings in- dicated the sex ratio for withdrawals was very similar to the enrolment sex ratio. Attrition rates from professional programs were lower than from programs where students tend to be less professionally committed. The bulk of withdrawals were first-year students with the rate of with- drawal generally being greatest early in the university session. The personal-reason category was most often given, followed closely by the academic, with the remaining being of much less relevance. These findings are discussed in relation to the structure of university programs, family and social pressures, and student needs.